Phosphorus Dynamics and Impacts on Potato Production in Northeast Florida - Joris Van Zeghbroeck; Guodong Liu; Yuncong Li (EDIS)
Florida is one of two states (FL and CA) that produce spring potatoes, FL having the highest crop value out of any state in the country ($469.67 per ton). Due to the low phosphorus use efficiency (PUE), high rates of phosphorus (P) are applied to ensure adequate yields. This has led to a buildup of legacy P, resulting in mehlich-1 levels as high as 375 mg kg-1. These levels are significantly higher than the critical values for potatoes (25-35 mg kg-1), yet farmers still report increased yields with P applications. Several organic amendments, management practices, and new fertilizers have been shown to help increase P availability in potato cropping systems by reducing P fixation and maximizing the available P fraction throughout the growing season. New fertilizers and management strategies should be researched in the TCAA to find methods that maintain yields while reducing the environmental impact of potato cropping systems.